Tanfīz Al-Tharīqah Al-Ihāiyyah Fī Ta'līm Al-Lugah Al-Arabiyyah - Chairani Astina (Pusat Studi Kependidikan (PSKp) Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Sains Al-Qur'an, 2019)
Teaching methods have been established and continued to be of particular importance to the classroom teaching process. Therefore, educators have concentrated most of their research efforts throughout the current century on the different teaching methods and their benefits in achieving desirable educational outcomes for students at different educational levels. This interest in teaching methods has led to the spread of saying that (the successful teacher is only a successful way), and those who train teachers to train their students to use different teaching methods that achieve the objectives of teaching easily and successfully, therefore, the oldest definitions of the teaching method refers to being the easiest ways to teach and learn. The suggestopedia method consists of a set of educational recommendations derived from the suggestive science that Luzanov described as